2018
DOI: 10.1017/jfm.2018.285
|View full text |Cite
|
Sign up to set email alerts
|

Secondary instabilities in the wake of an elongated two-dimensional body with a blunt trailing edge

Abstract: The secondary instability in the wake of a two-dimensional blunt body with a chord to thickness ratio of 46.5 was experimentally investigated for Reynolds numbers of 3500, 5200 and 7000 based on the blunt trailing edge height $h$. Planar, stereoscopic and high-speed particle image velocimetry (PIV) measurements were performed to characterise the wake and upstream boundary layer. The same mode B secondary instability that is found in the cylinder wake was found to be present in the wake of the elongated body st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(36 citation statements)
references
References 56 publications
(110 reference statements)
7
28
1
Order By: Relevance
“…It was shown that the use of POD misrepresents the structure of streamwise vortices when applied to streamwise velocity fields in the wake, and that the near-wake undulations in streamwise velocity only match the streamwise vortices when POD is not applied to the velocity fields beforehand. Considering direct measurements of the streamwise vortices and their temporal behaviour, Gibeau et al (2018) concluded the presence of mode B in the wake for a larger AR, and this was in contrast to the results of Naghib-Lahouti et al (2012, 2014. To our knowledge, no further experimental work regarding the streamwise vortices in the wakes of elongated blunt bodies has been carried out.…”
Section: Introductionmentioning
confidence: 59%
See 4 more Smart Citations
“…It was shown that the use of POD misrepresents the structure of streamwise vortices when applied to streamwise velocity fields in the wake, and that the near-wake undulations in streamwise velocity only match the streamwise vortices when POD is not applied to the velocity fields beforehand. Considering direct measurements of the streamwise vortices and their temporal behaviour, Gibeau et al (2018) concluded the presence of mode B in the wake for a larger AR, and this was in contrast to the results of Naghib-Lahouti et al (2012, 2014. To our knowledge, no further experimental work regarding the streamwise vortices in the wakes of elongated blunt bodies has been carried out.…”
Section: Introductionmentioning
confidence: 59%
“…While Gibeau et al (2018) showed that the analysis technique used by Naghib-Lahouti et al (2012, 2014 may have been flawed, the difference in AR between these two studies is too large to draw a conclusion for the lower AR investigated by Naghib-Lahouti et al (2012, 2014 and Ryan et al (2005). The present work seeks to remedy this by utilizing direct measurements of the streamwise vortices, i.e.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations